2004
DOI: 10.1021/jo0357622
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Conversion of β,γ-Unsaturated Silyl Sulfinates into (E)-Alkenes:  Asymmetric Synthesis of Polypropionate Fragments

Abstract: At low temperature, 1-alkoxy-1,3-dienes add to sulfur dioxide activated by a Lewis or protic acid generating zwitterionic intermediates that can be quenched by enoxysilanes. The resulting beta,gamma-unsaturated silyl sulfinates can be desilylated by 1:1 Pd(OAc)(2)/PPh(3) catalyst, liberating the corresponding beta,gamma-unsaturated sulfinic acids that undergo smooth and highly stereoselective retro-ene eliminations of sulfur dioxide. The method has been applied to generate enantiomerically pure polypropionate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…Although we have no proof for it, studies with trimethylsilyl 2-methylprop-2-enesulfinate have shown that Pd(OAc) 2 alone in MeCN does not catalyze the reaction. The presence of Ph 3 P and i-PrOH is crucial for success, and intermediacy of allyl-Pd species has been established [76]. The remarkable chirality transfer 26 to 27 strongly supports a mechanism in which Pd(0) adds oxidatively (retention of configuration) into the C-SO 2 SiMe 3 bond of 26 producing 33.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although we have no proof for it, studies with trimethylsilyl 2-methylprop-2-enesulfinate have shown that Pd(OAc) 2 alone in MeCN does not catalyze the reaction. The presence of Ph 3 P and i-PrOH is crucial for success, and intermediacy of allyl-Pd species has been established [76]. The remarkable chirality transfer 26 to 27 strongly supports a mechanism in which Pd(0) adds oxidatively (retention of configuration) into the C-SO 2 SiMe 3 bond of 26 producing 33.…”
Section: Introductionmentioning
confidence: 93%
“…Subsequent desulfinylation into 34 and protolysis of the Pd-SiMe 3 bond giving i-PrOSiMe 3 (driving force) is expected to generate hydride 35 that undergoes regioselective and stereoselective β-insertion of hydride into the allyl-Pd intermediate. An alternative mechanism is to invoke that the Pd(0) catalyst role is just to promote the Si-sulfinate bond cleavage that generates the corresponding β,γ-unsaturated sulfinic acids that in turn undergo classical retro-ene elimination of SO 2 producing 27 [76]. Further studies are obviously necessary for a better view.…”
Section: Introductionmentioning
confidence: 99%
“…For retro-ene desulfation of intermediates 20, recently developed conditions were applied successfully. [21] The use of previously described Et 3 NH + TfO À caused degradation, most probably because of b-elimination of the alkoxy group. 3-Acetoxydiene 5 f was slow to react and only 40 % of isomeric mixture was isolated together with unreacted starting material.…”
Section: Abstract In Frenchmentioning
confidence: 99%
“…Preliminary studies within our group [31] have shown that silyl sulfinate 13 reacts with PdA C H T U N G T R E N N U N G (OAc) 2 /Ph 3 P to give allylpalladium complex 15 and Me 3 SiOAc (Scheme 6). Complex 15 was then converted, at 25 8C, into sulfone 16.…”
Section: A C H T U N G T R E N N U N G [Pdcl 2 a C H T U N G T R E N mentioning
confidence: 99%